Mengukur Kemampuan Berpikir Kritis pada Materi Lingkungan Hidup dengan Taksonomi SOLO - Marhamah Marhamah (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2025)
The purpose of this study is to measure students' critical thinking skills on environmental material with SOLO taxonomy. Low critical thinking skills can be trained by applying the Problem Based Learning model combined with Group Investigation. Through this model students are trained to find environmental problems that exist around them through investigative activities, analyze these problems, and present them in front of the class. This research method is descriptive qualitative, with Lesson Study pattern. The research subjects were 30 second semester students. The instrument to measure critical thinking skills uses a test with indicators of providing arguments, evaluation, deduction, and induction. The assessment rubric refers to the SOLO taxonomy, consisting of five categories namely Prestructural, Semistructural, Unistructural, Multistructural, Relational, and Extended abstract. Data analysis was conducted using Gain score. The results of the study in LS 1 showed that students' critical thinking skills were in the Prestructural category as much as 2.75%, semistructural 15.06%, unistructural 52.05%, Multistructural 23.28%, and Relational 6.84%. The Gain score results show 0.30, included in the moderate category, meaning that there is an increase in critical thinking skills, namely at the relational and multistructural thinking stages.